Early Stage Rehabilitation for Strain Hamstring : A case report - Lucky Anggiat (Inspiree)
The  purpose  of  the study. This study's purpose is to report on the early stage physiotherapists' intervention on patients with hamstring strains as recommended in the early stage management of sports injuries.